Intervensi Audio Terapi Murottal Al-Quran pada Pasien Penyakit Jantung Koroner dengan Masalah Keperawatan Ansietas di Ruang ICU RSUD Dr. T.C.Hillers Maumere - Maria Mensiana; Ode Irman (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2023)
Coronary heart disease (CHD) is a disease that occurs due to decreased oxygen flow to the heart as a result of a buildup of plaque in the arteries. Patients with CHD usually feel afraid because they are exposed to the most vital parts of the body which can be at risk of death, this is what causes CHD patients to feel anxious. Anxiety that is not resolved can cause changes in heart rhythm which can make the patient's condition worse. One of the non-pharmacological techniques for dealing with anxiety is audio murottal Al-Quran therapy. The purpose of this case study was to determine the effect of murottal Al-Quran audio therapy on the anxiety level of CHD patients. The method used is descriptive method with a case study approach. The sampling technique was purposive sampling which met the inclusion criteria. The instrument used is State Trait Anxiety Inventory (STAI). The results of the application of murrotal audio therapy in CHD patients showed that there was a change where the patient's anxiety level decreased from moderate anxiety level (STAI score: 64) to not anxious (STAI score: 22). Conclusion: there is an effect of murrotal audio therapy on CHD STEMI patients in the ICU room of dr. T.C. Hillers Maumere .